Giardia and giardiasis 1 - Ganguly, Sandipan (Henry Stewart Talks, 2025)
Giardia: an enigmatic parasite, Diverse host range of Giardia spp., Life forms of Giardia: cyst and trophozoite, G. lamblia transmission cycle, Clinical manifestation, epidemiology and risk factors